Morphology, Age, and Growth of Triplophysa strauchii in Sayram Lake, Xinjiang, China - Zhengwei Wang; Huimin Hao; Jie Wei; Hao Wu; Syeda Maira Hamid; Ruixian Lv; Huale Lu; Zhulan Nie (Animals)
This study focused on T. strauchii in Sayram Lake, Xinjiang. In August 2023, a total of 768 samples were collected to investigate its morphological, age, and growth characteristics. T. strauchii has an elongated body with a slightly raised area behind the head. Its head is flat, the body is slender, the back contour is arc-shaped, the trunk is thick and round, and the tail is short. Principal component analysis (PCA) showed that the cumulative contribution rate of the first three principal components was 53.80%, which reflects the morphological characteristics of the species. Moreover, gender characteristics are not prominently manifested in external morphology. Discriminant analysis showed an accuracy rate of 51.80%, indicating that the accuracy of gender discrimination relying solely on external morphology is limited. The species’ age distribution ranges between 1 and 7 years old, with the dominant age around 3 years old, and age structure showing a unimodal distribution. The relationship between body length and body weight is W = 7.432 × 10−6L3.037(R2 = 0.995, n = 768). The exponent 3.037 indicates a growth pattern with priority given to body mass growth because it is greater than 3. The von Bertalanffy growth equation was selected to describe the growth of T. strauchii. The body length growth equation is Lt =139.346 [1 − e−0.267(t+1.639)], and the body mass growth equation is Wt = 27.79 [1 − e−0.267(t+1.639)]3.073. The inflection point age (ti) is 2.563, the growth coefficient (k) is 0.267, and the growth characteristic index(φ) is 3.715. The growth rate decreases with age, and the growth inflection point ages of males and females differ. The research findings provide basic data for population assessment, resource protection, and rational fishing in fishery resource management. This highlights the ecological adaptability of T. strauchii and emphasizes the importance of comprehensively considering multiple factors in fishery management.